Crises, changed leadership, change management and educational technology - Waghid, F. (South African Journal of Higher Education, 2023)
Higher education has been challenged in recent years to reimagine itself in response to a shifting labour market. It is argued that Educational Technology (EdTech) as a democratised form of teaching and learning may assist higher education institutions in their efforts to produce graduates who are able to successfully navigate the current labour market. However, the adoption of EdTech has been slow. This could be attributed to a lack of urgency, resulting in a state of complacency in higher education. It is argued that change management must facilitate EdTech adoption and implementation. The change management model utilised in this article is based on John Kotter’s eight-step approach. This approach uses a crisis to emphasise the need for change. In the absence of a perceivable crisis, the approach also considers how complacency can be reduced to ensure that change is driven by urgency. In addition, it is argued that change management requires changed leadership, an ethical form of leadership, in order to support change management initiatives.